ANALISIS KEBUTUHAN PENGEMBANGAN E-HANDOUT MATERI PROSES FOTOSINTESIS PADA TUMBUHAN BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN BURENGAN 2 - Rani, Yolanda Surya; Primasatya, Nurita; Kurnia, Ita (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
Abstract: Needs analysis is the initial stage used to determine the problems that exist in learning in a school. The purpose of this study was to obtain information about the needs analysis of e-handout teaching materials on photosynthesis process material in plants in class IV SDN Burengan 2. The method used in this research is descriptive and uses quantitative scores or analysis. The subjects of this study consisted of principals, teachers, and fourth grade students of SDN Burengan 2 Kediri City. Data collection was carried out using interviews, questionnaires, and observation techniques. The problems in this study are the lack of reading related to the material, lack of student understanding of the process of photosynthesis in plants, a total of 30 out of 56 students still get scores below the KKTP (Criteria for Achieving Learning Objectives), the lack of teaching materials used, and the lack of project activities on the material of the photosynthesis process in plants. Based on the results of the needs analysis, it can be concluded that the development of e-handout material on the process of photosynthesis in plants based on project-based learning is needed to improve the learning outcomes of fourth grade students of SDN Burengan 2. This research can be developed to the e-handout development stage for maximum results. Keywords: needs analysis, e-handout, photosynthesis process in plants, 4th grade, SDN Burengan 2